Thin on the ground : Neandertal biology, archeology and ecology - Churchill, Steven Emilio (Ames, Iowa : Wiley-Blackwell, 2014)
"Thin on the Ground: Neandertal Biology, Archeology and Ecology synthesizes the current knowledge about our sister species the Neandertals, combining data from a variety of disciplines to reach a cohesive theory behind Neandertal low population densities and relatively low rate of technological innovation. The book highlights and contrasts the differences between Neandertals and early modern humans and explores the morphological, physiological, and behavioral adaptive solutions which led to the extinction of the Neandertals and the population expansion of modern humans. Written by a world recognized expert in physical anthropology, Thin on the Ground: Neandertal Biology, Archaeology and Ecology will be a must have title for anyone interested in the rise and fall of the Neandertals"--
"Integrates current understanding of the biology, archeology, and ecology of Neandertals"--
Machine generated contents note: Chapter 1: Thin on the Ground: Population Density and Technological Innovation Chapter 2: The Neandertals in Time and Space Chapter 3: The Body Neandertal Chapter 4: Surviving the Cold Chapter 5: The Caloric Economy of Pleistocene Europe Chapter 6: Neandertals as Consumers Chapter 7: Red in Tooth and Claw: Neandertals as Predators Chapter 8: In the Company of Killers: Neandertals as Carnivores Chapter 9: The Cost of Living in Ice Age Europe Chapter 10: Neandertal Life, Life History, and Demography Chapter 11: From Thin to Thick: The African MSA .
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher.
Keywords: Neanderthals; Paleolithic period; Human evolution; SOCIAL SCIENCE / Anthropology / Physical; Human evolution; Neanderthals; Paleolithic period; NATURE / Animals / Mammals; SCIENCE / Life Sciences / Zoology / Mammals; Electronic books